Expression of a new serpin gene screening from metagenomics database in \(Pichia pastoris\) and some characterization of recombinant protein - Cuong, Pham Viet; Hong, Tran Thi (Academia Journal of Biology, 2021)
Currently, searching for new protease inhibitors is of interest to many scientists around the world because they play an important role in controlling harmful proteases. As terrestrial bioactive resources are becoming increasingly depleted, studies are aimed at finding other sources, for example, the ocean. Some recent reports indicate that sponge- associated microbes produce substances with high biological activity, such as anticancer and anti-inflammation, protease inhibition, etc. In this report, a new serpin gene screened from the metagenomics database of microorganism-associated Spheciospongia vesparium QT2 collected sea of Quang Tri province (Vietnam), was successful expressed in Pichia pastoris SMD1168. The obtained result showed that the maximum amount of recombinant protein secreted in the medium was received after 72 hours of induction with methanol. The PAGE electrophoresis supplemented with 0.1% casein and the Trypsin-sepharose 4B affinity chromatography column were performed, and the result was confirmed that the recombinant protein expressed in the P. pastoris SMD1168 (molecular weight about 50 kDa) was the target protein. The purified recombinant protein PI-QT exhibited inhibitor activity on trypsin, ɑ-chymotrypsin and thermolysin and the inhibition was 88.7%, 69% and 43%, respectively. In addition, PI-QT protein is stable and has optimal activity in the pH range 7−9, the temperature is below 60 oC.